2005
DOI: 10.1371/journal.pgen.0010043
|View full text |Cite
|
Sign up to set email alerts
|

Gain and Loss of Multiple Genes During the Evolution of Helicobacter pylori

Abstract: Sequence diversity and gene content distinguish most isolates of Helicobacter pylori. Even greater sequence differences differentiate distinct populations of H. pylori from different continents, but it was not clear whether these populations also differ in gene content. To address this question, we tested 56 globally representative strains of H. pylori and four strains of Helicobacter acinonychis with whole genome microarrays. Of the weighted average of 1,531 genes present in the two sequenced genomes, 25% are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
222
2
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 207 publications
(253 citation statements)
references
References 63 publications
(80 reference statements)
26
222
2
3
Order By: Relevance
“…The variable genome is composed of genes not found in all strains, either because genes are gained through horizontal gene transfer or because they are differentially lost. Every unique microbial strain sequenced contains a different suite of variable genes (2,(4)(5)(6)(7)(8)(9)(10)(11). Yet, the ecological forces that define the distribution of these variable genes among strains, the sources of genetic material, and the rates at which genes are acquired and lost are unknown.…”
Section: Fig 1 Schematic Representations Of S1p and Lt1009 (A)mentioning
confidence: 99%
“…The variable genome is composed of genes not found in all strains, either because genes are gained through horizontal gene transfer or because they are differentially lost. Every unique microbial strain sequenced contains a different suite of variable genes (2,(4)(5)(6)(7)(8)(9)(10)(11). Yet, the ecological forces that define the distribution of these variable genes among strains, the sources of genetic material, and the rates at which genes are acquired and lost are unknown.…”
Section: Fig 1 Schematic Representations Of S1p and Lt1009 (A)mentioning
confidence: 99%
“…ORFs that are present in the former data set and absent from the latter are listed above, and the hypothetical proteins without assignable COGs are listed in Table 7. Because Gressmann et al (33) used DNA microarrays consisting of 26695 and J99 ORFs, we converted the 1,150 ''universally present'' ORFs to HPAG1 gene identifiers to perform the comparison. Among the 1,150 ORFs, 1,146 are represented in the HPAG1 genome.…”
Section: Resultsmentioning
confidence: 99%
“…5 and 6, which are published as supporting information on the PNAS web site). The 1,025-member ChAG gene ''signature'' was further distilled by comparing it to the H. pylori ''pan-genome'' defined by Gressmann et al (33) from their analysis of 56 ''global'' H. pylori strains. Their analysis was based on DNA microarrays containing PCR products from 98% of the ORFs present in the 26695 and J99 genomes.…”
Section: Resultsmentioning
confidence: 99%
“…For example, by genome comparisons of eight chronic atrophic gastritis strains, it was found that many R-M systems are associated with this condition (204,205). Some of these chronic atrophic gastritis-associated enzymes were also found to be pH regulated (205).…”
Section: R-m Systems Of Helicobacter Pylorimentioning
confidence: 99%